116k views
21 votes
Write the trinomial as a square of a binomial or as an expression opposite to a square of a binomial: 4cd -25c^2 -0.16d^2

User Caopeng
by
4.5k points

1 Answer

7 votes

Answer:

= -(5c - 0.4d)^2

Explanation:

4cd - 25c^2 - 0.16d^2

= 4cd - (5c)^2 - (0.4d)^2

= -[(5c)^2 -2*5*0.4cd + (0.4d)^2]

= -[(5c)62 - 2*(5c)*(0.4d) + 0.4d)^2]

= -(5c - 0.4d)^2

User DejanRistic
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.